PENGARUH LDR, NPL DAN BOPO TERHADAP PROFITABILITAS LPD DI KOTA DENPASAR TAHUN 2017-2019 - Adnyana Puta, I Made Dwi; Suryanawa, I Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.03.TAHUN.2022DO - 10.24843/EEB.2022.v11.i03.p08, 2022)
This study aims to determine the effect of loan to deposit ratio, non-performing loans, operational costs and operating income on profitability. This research was conducted at LPDs in Denpasar City in 2017-2019. The number of samples used as many as 35 LPD, with saturated sampling method. The data collection method used is the non-participant observation method, namely through observations made on the LPD financial report data publication documents. The types of data are quantitative and qualitative data. Sources of data used are secondary data obtained from the LPLPD Denpasar City. The analysis technique used is multiple linear regression analysis technique. The results of this study provide evidence that the loan to deposit ratio has a positive and significant effect on the profitability of LPDs in Denpasar City, non-performing loans and operational costs of operating income have a negative and significant effect on the profitability of LPDs in Denpasar City.